1999
DOI: 10.1159/000006870
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isosorbide-5-Mononitrate on Exercise Performance and Clinical Status in Patients with Congestive Heart Failure

Abstract: Background and Aims: Nitrate therapy improves hemodynamics in patients with heart failure, but the chronic effects of oral nitrates on exercise performance and clinical status have not been well studied. Methods: Oral isosorbide-5-mononitrate (ISMN) (50 mg once daily) or placebo was administered to 136 patients (NYHA Class 2–3) treated for heart failure, all receiving captopril and most also furosemide. Endpoints were treadmill exercise time at 12 weeks by modified Naughton protocol (primary), with an addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…We have demonstrated that the addition of nitrates to a baseline therapy with captopril and diuretics does not improve exercise tolerance of patients with mild-to-moderate heart failure from coronary disease [5]. This is in agreement with a study by Lewis et al [6]who found no effect of isosorbide-5-mononitrate on treadmill exercise time in their study group as a whole while patients with a lesser reduction in left-ventricular ejection fraction might benefit from the addition of nitrates. The objective of this substudy of our preceding study [5]was to evaluate the effects of stopping nitrate therapy on left-ventricular volume at rest and during exercise.…”
Section: Introductionsupporting
confidence: 89%
“…We have demonstrated that the addition of nitrates to a baseline therapy with captopril and diuretics does not improve exercise tolerance of patients with mild-to-moderate heart failure from coronary disease [5]. This is in agreement with a study by Lewis et al [6]who found no effect of isosorbide-5-mononitrate on treadmill exercise time in their study group as a whole while patients with a lesser reduction in left-ventricular ejection fraction might benefit from the addition of nitrates. The objective of this substudy of our preceding study [5]was to evaluate the effects of stopping nitrate therapy on left-ventricular volume at rest and during exercise.…”
Section: Introductionsupporting
confidence: 89%
“…A total of 14 studies were included in the meta-analysis of adverse events. All-cause mortality was reported in 10 studies, 18 20 , 22 25 , 27 , 29 , 30 which all compared nitrate with control treatments. A low heterogeneity between studies was found.…”
Section: Resultsmentioning
confidence: 99%
“…Arrhythmia was reported in three studies. 24,29,32 No significant heterogeneity between studies was found. Therefore, the fixed-effects model was used.…”
Section: Arrhythmiamentioning
confidence: 94%
See 1 more Smart Citation
“…In a double‐blind, placebo‐controlled study of 136 patients with NYHA functional class II‐III cardiac failure, 31 ISMN‐SR 50 mg was added to captopril for 12 weeks. Patients were subdivided into those with entry LVEF of 20‐30% or 31‐40%.…”
Section: Isosorbide Mononitrate In Heart Failurementioning
confidence: 99%